Key elements of digital literacy in Malaysian technological learning - Chin, Esther Tze-N (2024)
The 21st century has seen a significant increase in the use of technology in education, especially in Malaysia. The recent Covid-19 pandemic has accelerated this trend, making digital literacy a crucial skill for both Malaysian students and Educators, especially at the tertiary level. However, while the importance of digital literacy is well recognized, the specific aspects of digital literacy that are essential for tertiary education are not well defined. This study aims to discover what is the digital literacy level of Malaysian University students, using Universiti Tunku Abdul Rahman as a sample. The study also aims identify the key elements of digital literacy that are vital for tertiary education in Malaysia. The study achieves this through a set of semi-structured interviews to obtain a set of qualitative data, which would then be put through thematic analysis and analysed to draw the related conclusions. The study concludes that digital literacy is crucial for students to succeed in tertiary education and highlights the specific aspects of digital literacy that students and educators should focus on to aid in students’ pursuit of higher education. The study also highlights the challenges faced in researching digital literacy, and how future research could help devise better strategies to aid in improving the overall digital literacy level of tertiary educational students.